HUBUNGAN DISIPLIN BELAJAR DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PRODUKTIF TATA KECANTIKAN RAMBUT SMK NEGERI 6 PADANG TAHUN AJARAN 2014/2015 - Sari, Wulan Filta; Rostamailis, Rostamailis; Yanita, Merita (Journal of Home Economics and Tourism, 2015)
This article aims to determine the tendency of learningdiscipline and student learning outcomes in subjects productive. Thistype of research is a descriptive quantitative approach of Ex PostFacto. Population in this research is grade X, XI, and XII in BeautyHairstyling Subject of SMK Negeri 6 Padang that totaling 76 peoplesand samples taken for about 46 peoples from part of the population.Data were analyzed using the percentage of Achievement LevelRespondents (ALR), correlation analysis using Pearson ProductMoment Correlation and continued with T test. The results showedthat, the percentage of respondents' level of achievement in thediscipline of learning 57% with low category. While the results ofstudy subjects known to the average productive learning outcomeslowest is 65 whereas the highest learning outcomes is 95. Bivariatecorrelation analysis was obtained by 0.614 indicating a strongassociation occurs, the significance test of correlation shows the pricet count > t label (14, 548 > 2.021) which means that there aresignificant Ha who reads the discipline of learning to the learningoutcomes of students earning subjects Subject Tata Beauty SMKNegeri 6 Padang received the 95% significance level.Keywords: Discipline learning, learning outcomes, productivelesson, hairstyling.